2021
DOI: 10.3390/jcm10153264
|View full text |Cite
|
Sign up to set email alerts
|

Resting Heart Rate and Cardiovascular Outcomes during Intensive and Standard Blood Pressure Reduction: An Analysis from SPRINT Trial

Abstract: The association between elevated resting heart rate (RHR) as a cardiovascular risk factor and lowering of systolic blood pressure (SBP) to currently recommended values remain unknown. Systolic Blood Pressure Intervention Trial (SPRINT) data obtained from the NHLBI were used to describe the relationship between RHR and SBP reduction to <120 mmHg compared to SBP reduction to <140 mmHg. The composite clinical endpoint (CE) was defined as myocardial infarction, acute coronary syndrome, decompensation of hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Both RHR and VVHRV were proven to be positively associated with the risk of cardiovascular outcomes. A sub-study of the SPRINT randomized controlled trial found that the increase in the risk of composite cardiovascular events toward elevated baseline RHR was more potent in hypertensive subjects received intensive blood pressure treatment, compared to those with standard blood pressure treatment ( 10 ). However, the effect of intensive blood pressure control on VVHRV remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both RHR and VVHRV were proven to be positively associated with the risk of cardiovascular outcomes. A sub-study of the SPRINT randomized controlled trial found that the increase in the risk of composite cardiovascular events toward elevated baseline RHR was more potent in hypertensive subjects received intensive blood pressure treatment, compared to those with standard blood pressure treatment ( 10 ). However, the effect of intensive blood pressure control on VVHRV remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The Systolic Blood Pressure Intervention Trial (SPRINT) trial showed that intensive blood pressure control showed significant better cardiovascular outcomes, after which the American hypertension guideline quickly reduced the blood pressure target ( 8 , 9 ). Sobieraj et al reported a more potent increase in cardiovascular risk associated with higher RHR in the intensive blood pressure treatment than in the standard treatment group ( 10 ). However, whether long-term RHR variability affected the benefit of intensive blood pressure control remained unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Heart rate (HR) is regulated by both sympathetic and parasympathetic nerves, with sympathetic overactivation causing an increase in HR and parasympathetic nerves acting in the opposite direction ( 7 ). Increased resting HR is associated with high cardiovascular morbidity and mortality ( 8 ). In a high-risk population where 75% had hypertension, increased HR is an independent risk factor for the development of heart failure ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Temporal changes in HR are also associated with mortality, heart attack, and stroke in the Atherosclerosis Risk in Communities Study ( Vazir et al, 2018 ). Additionally, the Systolic Blood Pressure in Intervention Trial indicated higher RHR increased cardiovascular risk ( Sobieraj et al, 2021 ). Therefore, overall suggestion of managing increasing RHR and BP is complex due to lack of clinical guidelines, although the LIFE study shows that increased RHR by 10 beats per minute increases cardiovascular mortality ( Okin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%